Comparison between NIR and UVVIS spectra chemometrics for predicting FCC feedstocks properties - Baldrich, Carlos A.; Novoa, Luz A.; Bueno, Alexis (CT&F - Ciencia, Tecnología y Futuro, 2010)
In this paper a comparison is made between the performance of models developed by applying chemometric analysis to NIR and UVVIS spectral data obtained from feedsctock samples corresponding to the different Ecopetrol S.A., Barrancabermeja Refinery FCC units for predicting some important physicochemical properties. The results show the utility of both methodologies here evaluated to follow up the quality of these types of refinery streams and present the advantages and disadvantages of each methodology for predicting the feedstock properties here evaluated.